2020
DOI: 10.1152/jn.00322.2020
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of finger enslaving: control with referent coordinates and effects of visual feedback

Abstract: When a person tries to press with a finger, other fingers of the hand produce force unintentionally. We explored this phenomenon of enslaving during unintentional force drifts in the course of continuous force production by pairs of fingers of a hand. Healthy subjects performed accurate force production tasks by finger pairs Index-Middle, Middle-Ring, and Ring-Little with continuous visual feedback on the combined force of the instructed (master) fingers or of the non-instructed (enslaved) fingers. The feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 83 publications
1
5
0
Order By: Relevance
“…The drifts in the other force variable could be up or down, but across all conditions, the relative amount of enslaved force increased. This increase in enslaving was large in magnitude (on the order of 25% over 10 s) as illustrated in Figure 6 (Abolins et al, 2020b;Hirose et al, 2020). Similar drifts in enslaving were observed during tasks performed by different finger pairs of the hand, Index + Ring, Middle + Ring, Index + Middle, and Ring + Little.…”
Section: Recent Studies Of Drifts In Enslavingsupporting
confidence: 65%
See 4 more Smart Citations
“…The drifts in the other force variable could be up or down, but across all conditions, the relative amount of enslaved force increased. This increase in enslaving was large in magnitude (on the order of 25% over 10 s) as illustrated in Figure 6 (Abolins et al, 2020b;Hirose et al, 2020). Similar drifts in enslaving were observed during tasks performed by different finger pairs of the hand, Index + Ring, Middle + Ring, Index + Middle, and Ring + Little.…”
Section: Recent Studies Of Drifts In Enslavingsupporting
confidence: 65%
“…In stark contrast to this assumption, a series of recent studies have demonstrated unintentional (and unperceived!) drifts in enslaving that happen over very brief time intervals (Abolins et al, 2020b;Hirose et al, 2020;Ricotta et al, 2021). These observations have documented a large increase in indices of enslaving highly consistent across conditions and subjects.…”
Section: Recent Studies Of Drifts In Enslavingmentioning
confidence: 70%
See 3 more Smart Citations